Patients behind the front lines: the exchange of mentally-ill patients in the 1948 Arab–Israeli War. Issue 3 (September 2020) - Argo, Daniel; Fainstein, Vladislav; Jones, Edgar; Abramowitz, Moshe Z
The British Mandate in Palestine ended abruptly in 1948. The British departure engendered a complex situation which affected all areas of life, and the country's health system was no exception. Gradual transition of the infrastructure was almost impossible owing to the ineffectiveness of the committee appointed by the United Nations. The situation was further complicated by the outbreak of the Arab–Israeli War. We relate for the first time the story of 75 Jewish patients who were left in a former British mental hospital in Bethlehem – deep behind the front lines. Despite the hostilities, there were complex negotiations about relocating those patients. This episode sheds light on the Jewish and Arab relationship as it pertained to mental institutions during and immediately after the British Mandate.